REPRESENTATION OF MADURA WOMEN IN THE HOUSEHOLD (International Conference of Graduate School on Sustainability (ICGSS), 2018)
Madura in socio-cultural reality, hides mysteries in the form of individual local and collective interactional values, so it is very feasible to exposed its existence as an important part of the social-humanities problem. Mainly concerning the representation of gender bias in women in a Madura household, and it becomes very interesting to explore more deeply in terms of its social role. The use of functional structural perspectives with a focus on individual roles has facilitated the description of various forms of habits and the dynamics of social relations that develop in the social environment. Qualitative descriptive methods used in this study, try to interpret the social reality that occurs in Madura women, both internal and external relations related to the household. The results of this study indicate that Madura is an ethnic group that is very thick with Islamic culture and religion. As well as, there is still a gender bias for women, because men are free to get involved in the public sphere, while women are severely restricted in their participation in the public sphere. In the scope of the domestic sector in Madura women, it still dominates the habit of daily living compared to the public sector, and prioritizes family matters. This is shown by the obedience of Madura women to their husbands, because birth and inner life are the most basic responsibilities for husbands.